Hemato-Oncological Diseases as Risk Factor for Recurrence or Metastasis of Pleomorphic Dermal Sarcoma - Helbig, Doris (Frontiers in Oncology, 2022)
Background: Atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) are increasing sarcomas of the skin with a genetic UV signature. Immunosuppression is a known risk factor for developing other UV-induced skin cancers such as cutaneous squamous cell carcinomas (cSCC), basal cell carcinomas (BCC) and Merkel cell carcinomas with increased mortality. In case reports or small case series of AFX/PDS patients, immunosuppression has been hypothesized as a risk factor for the development of distant metastases. The aim of the present study was to analyse immunosuppression as a risk factor for AFX/PDS in a large patient cohort. Methods: A cohort of 164 patients with AFX/PDS (47 AFX, 117 PDS) were collected between 2003 and 2021 and analyzed for clinicopathological data with special focus on immunosuppression. Results: 29.9% of all patients had any kind of immunosuppression. 6.4% of the AFX and 12.0% of the PDS patients had underlying hemato-oncological diseases. Patients with an immunosuppression due to an underlying hemato-oncological disease had a significant increased risk to progress (p= 0.010) and to develop distant organ metastases (p= 0.000). Conclusions: Immunosuppression seems to be a risk factor for developing AFX/PDS with worse clinical outcome. Therefore, immunosuppression, especially underlying hemato-oncological diseases, should be considered in the treatment and follow-up care of patients with AFX/PDS.